Dampak Maraknya Bank Keliling Bank Emok di Kalangan masyarakat Bungursari Kota Tasikmalaya : Apa itu bank emok? - Hasna Gustiani (ORGANIZE: Journal of Economics, Management and Finance, 2023)
Emok Bank is a term for a microfinance business that lends money to the public using a group lender system that is done every week. The existence of emok bank in Bungursari, Bungursari Village, Bungursari District, Tasikmalaya City is used by the community as one of the supports for economic activity. Emok Bank provides an easy loan process that is carried out. This is what makes the emok bank still have an existence in the midst of the many financial sectors, both formal and informal, that are offered in Bungursari Village. The aim of the research was to find out the mechanism of emok bank loans in Bungursari Village, Bungursari Village, Bungursari District, Tasikmalaya City and what kind of social impact was felt by the Bungursari community. As well as to find out the actions of the local government in an effort to eradicate Bank Emok. The results of the study explained that the people of Bungursari Village, Bungursari Village, Bungursari District, Tasikmalaya City carried out a loan mechanism at the emok bank through several stages. The community also has dependence on emok banks due to economic factors and administrative aspects as well as changes in social and economic conditions that reduce living standards. Bank emok has been considered as the easiest initial alternative in lending. The selection was also based on how many people practice loans at emok banks. This is what ultimately causes loans to emok banks to be considered normal. The emok bank in Bungursari Village seems to have become an alternative to support the community's economic needs. The local government has also taken preventive measures to eradicate the emok bank by holding joint deliberations and forming community programs such as cooperatives ABSTRAK Bank Emok merupakan sebutan bagi usaha keuangan mikro yang meminjamkan uang kepada masyarakat dengan sistem tagihan secara berkelompok (group lender) yang dilakukan setiap mingguan. Keberadaan bank emok di Bungursari, Kelurahan Bungursari, Kecamatan Bungursari, Kota Tasikmalaya dimanfaatkan masyarakat sebagai salah satu penopang aktifitas ekonomi. Bank emok memberikan suatu kemudahan proses peminjaman yang dilakukan. Hal ini yang membuat bank emok tetap mempunyai eksistensi di tengah banyaknya sektor finansial baik formal ataupun informal yang ditawarkan di Kampung Bungursari. Penelitian yang dilakukan bertujuan untuk mengetahui mekanisme pinjaman bank emok di Kampung Bungursari, Kelurahan Bungursari, Kecamatan Bungursari, Kota Tasikmalaya dan seperti apa dampak sosial yang dirasakan masyarakat Bungursari. Serta untuk mengetahui tindakan pemerintah setempat dalam upaya untuk memberantas Bank Emok. Hasil penelitian menjelaskan bahwa masyarakat Kampung Bungursari, Kelurahan Bungursari, Kecamatan Bungursari, Kota Tasikmalaya melakukan meknisme peminjaman pada bank emok melalui beberapa tahap. Masyarakat pun memiliki ketergantungan terhadap bank emok disebabkan karena faktor ekonomi dan aspek administrasi serta terjadinya perubahan kondisi sosial, ekonomi yang menurunkan taraf hidup. Bank emok telah dianggap sebagai suatu alternatif awal yang paling mudah dalam peminjaman. Pemilihan tersebut juga didasarkan banyak masyarakat yang mempraktikan pinjaman pada bank emok. Hal tersebut yang akhirnya menyebabkan pinjaman pada bank emok dianggap biasa. Bank emok di Kampung Bungursari seolah telah menjadi alternatif untuk menopang kebutuhan ekonomi masyarakat. Pemerintah setempat pun telah melakukan tindakan upaya pencegahan untuk memberantas bank emok tersebut dengan melakukan musyawarah bersama serta membentuk program masyarakat seperti koperasi